Efficacy of ChatGPT in Educating Patients and Clinicians About Skin Toxicities Associated With Cancer Treatment - Annie Chang; Jade Young; Andrew Para; Angela Lamb; Nicholas Gulati (JMIR Dermatology)
AbstractThis study investigates the application of ChatGPT, an artificial intelligence tool, in providing information on skin toxicities associated with cancer treatments, highlighting that while ChatGPT can serve as a valuable resource for clinicians, its use for patient education requires careful consideration due to the complex nature of the information provided.